Creating Instructional Audios to Enhance University Students’ Instruction in the midst of Large Student Numbers - Manu, Jacob; Antwi, Samuel (Journal of Education and Practice, 2025)
Purpose: The purpose of the current study was to investigate the creation and use of instructional audios at the institutions of higher learning in Ghana and the experiences of university students after being exposed to instructional audios based on five multimedia design principles to augment the teaching of the introduction to information and communication technology course (GPD 112, year one course) in the 2022/2023 academic year. Methodology: With the use of segmentation, personalisation, learner-control, coherence and redundancy principles of multimedia design according to Clark and Mayer (2011), instructional audios were created and shared on students’ WhatsApp platform for them to review before the next class. After 10 weeks into the semester, over 1600 learners responded to a 15-item questionnaire. Findings: The major findings were that: over 97.3% of university students use smartphone. Second, over 70% of students have not been exposed to the use of instructional audios in their teaching and learning process. Third, 84% of the students confirmed that the availability of the instructional audios helped them to learn meaningfully. Unique contribution to Theory, Policy and Practice: Finally, as much as 88% of the university students indicated their willingness to recommend the use of the instructional audios to their friends. With renewed interest in instructional audios use, students can better understand their lecturers beyond the lecture halls. Other implications for practice are discussed.